2003
DOI: 10.1046/j.1365-2702.2003.00703.x
|View full text |Cite
|
Sign up to set email alerts
|

Observations, confirmations and strategies – useful tools in decision‐making process for nurses in practice?

Abstract: The aim of the study was to describe how nurses make decisions on measures in clinical practice. The data-collection method consisted of audio-taped interviews with six nurses. The interviews were then transcribed verbatim. The questions in the interviews were based on nursing situations observed earlier when the nurses initiated and implemented patient-related measures and the focus was on the nurses' experience of decision making. A content analysis was performed. The results show that the nurses' decisions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
0
12

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(70 citation statements)
references
References 24 publications
4
54
0
12
Order By: Relevance
“…The characteristics of the stimuli in the simulated task environment and their relationship to performance have been clearly documented in the literature. [35][36][37] The results of the current study mirror those seen in studies of nurses with different levels of experience (e.g., novice versus expert), with the performance by the second-degree students reflecting the performance of more experienced practitioners. [35,38] Overall, the performance differences seen between the two groups are supportive of the notion that second-degree programs develop individuals with key advantages in decision-making capacity.…”
Section: Discussionsupporting
confidence: 73%
“…The characteristics of the stimuli in the simulated task environment and their relationship to performance have been clearly documented in the literature. [35][36][37] The results of the current study mirror those seen in studies of nurses with different levels of experience (e.g., novice versus expert), with the performance by the second-degree students reflecting the performance of more experienced practitioners. [35,38] Overall, the performance differences seen between the two groups are supportive of the notion that second-degree programs develop individuals with key advantages in decision-making capacity.…”
Section: Discussionsupporting
confidence: 73%
“…Whereas (O'Connell, 2000) found that nurses make sense of the situation to minimize uncertainty by adapting work practices through collecting required information and prioritize patient care plan. While (Cioffi, 1998;Benner et al, 1999;and Hedberg & Larsson, 2003) found that nurses rely on experience to make their clinical decisions when facing uncertain situation. Adding to that (Carr et al, 2001) found that to buffer the effect of uncertainty nurses participate patients in decision-making if collaboration with colleagues was not available.…”
Section: Discussionmentioning
confidence: 99%
“…Adding to that (Carr et al, 2001) found that to buffer the effect of uncertainty nurses participate patients in decision-making if collaboration with colleagues was not available. Furthermore (Hedberg and Larsson, 2003) found that collaboration with colleagues and information gathering reduce nurses' uncertainty. Also (Vaismoradi et al, 2011) revealed that losing sensitivity and avoiding trouble practice were main strategies nurses used to deal with uncertain situations in practice.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Smith (1988) employed six purposively selected nurses, Hedberg and Larsson (2003) employed six samples in their study. However, increasing the sample size will enrich and deepen discussions of intuitive decision-making processes.…”
Section: Conclusion and Suggestionsmentioning
confidence: 99%